2021
DOI: 10.1016/j.jbiotec.2021.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of a functional algal-expressed TGF-β mimic halts colitis in a murine DSS model

Abstract: Inflammatory bowel disease (IBD) is a set of immunological disorders which can generate chronic pain and fatigue associated with the inflammatory symptoms. The treatment of IBD remains a significant hurdle with current therapies being only partially effective or having significant side effects, suggesting that new therapies that elicit different modes of action and delivery strategies are required. TGM1 is a TGF-β mimic that was discovered from the intestinal helminth parasite Heligmosomoides polyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 74 publications
(88 reference statements)
1
14
1
Order By: Relevance
“… 127 A Heligmosomoides polygyrus TGF-β mimic can directly bind to TGF-β receptors in humans and mice, and induce differentiation of Treg cells, which alleviates pathological damage in the allograft rejection and DSS-induced colitis models in mice. 128 , 129 Cell therapy using Treg cells to treat allergic asthma has been reported. Adoptive transfer of Treg cells from Trichinella spiralis -infected mice to OVA-treated mice showed significant anti-inflammatory effects.…”
Section: The Immunoregulatory Mechanisms Of Identified Helminth-derived Moleculesmentioning
confidence: 99%
“… 127 A Heligmosomoides polygyrus TGF-β mimic can directly bind to TGF-β receptors in humans and mice, and induce differentiation of Treg cells, which alleviates pathological damage in the allograft rejection and DSS-induced colitis models in mice. 128 , 129 Cell therapy using Treg cells to treat allergic asthma has been reported. Adoptive transfer of Treg cells from Trichinella spiralis -infected mice to OVA-treated mice showed significant anti-inflammatory effects.…”
Section: The Immunoregulatory Mechanisms Of Identified Helminth-derived Moleculesmentioning
confidence: 99%
“…In recent studies, we have shown that TGM can mediate suppression of immune inflammation, for example in models of airway allergy (Chauché et al, 2022). We also established the ability of TGM to abate the severity of DSS colitis in mice, using high doses delivered orally through admixture with drinking water (Smyth et al, 2021). Focusing on colitis, we now evaluate in more depth the relative potencies of HES and TGM, using several different murine models of colitis (Kiesler et al, 2015), including inflammation induced with TNBS, and a T cell transfer model in which adaptive immune responses to intestinal antigens more closely represents human disease.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Administration of recombinant S. japonicum cystatin also reduced inflammatory parameters and ameliorated the severity of the trinitrobenzene sulfonic acid (TNBS)-induced colitis ( 81 ). HpTGM from H. polygyrus is a TGF-β mimicry and suppresses intestinal inflammatory response ( 5 , 82 ). In Smyth’s study (2020), active HpTGM was recombinantly expressed by Chlamydomonas reinhardtii in order to be safely consumed orally in mice and humans.…”
Section: Potential Of Parasite-derived Immunomodulators As Drugs For ...mentioning
confidence: 99%
“…In Smyth’s study (2020), active HpTGM was recombinantly expressed by Chlamydomonas reinhardtii in order to be safely consumed orally in mice and humans. Oral administration of recombinant HpTGM regulated immune cells and ameliorated weight loss, lymphadenopathy, and disease symptoms in a mouse model of DSS-induced colitis ( 82 ).…”
Section: Potential Of Parasite-derived Immunomodulators As Drugs For ...mentioning
confidence: 99%